On Theodicy and Veijola’s Linkage of Genesis 22 to the Book of Job - Lombaard, Christo (Usuteaduslik Ajakiri, 2020)
In this brief Ideengeschichte, the cultural construct of Western(ised) questions on theodicy, namely Gottfried Wilhelm Leibniz’s 1710 Essais de Théodicée, the Hebrew Bible Book of Job and the understanding of Timo Veijola on Genesis 22 as a precursor to the Book of Job, are brought into discussion with one another. The impossibility of extracting ourselves from our matrices of understanding makes it difficult to understand matters of holiness as anything other than as matters of theodicy.